Genetic Variation of Golden Silk-Producing Insect Cricula trifenestrata Helf. (Lepidoptera: Saturniidae) Using ISSR (Inter Simple Sequence Repeats) Molecular Marker - Agnes Herlina Dwi Hadiyanti (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2018)
The aims of this research were to conduct a study on genetic variation C. trifenestrata collected from several sampling locations using ISSR (Inter-Simple Sequence Repeat) molecular markers. The applied methods of the research were to collect samples (C. trifenestrata), isolation DNA genome, and analysis of genetic variation using the ISSR-PCR method. Based on genetic variation analysis using 4 primers (ISSR 1, ISSR 2, ISSR 6, dan ISSR 7), it is known that the level of genetic variation and polymorphism of C. trifenestrata is high with a percentage of 98.9%. The formed dendogram showed that the 29 studied samples of C. trifenestrata separate into two major groups at the similarity level of (0,60) 60%.